Association between alcohol-induced erythrocyte membrane alterations and hemolysis in chronic alcoholics - Bulle, Saradamma; Reddy, Vaddi Damodara; Maturu, Paramahamsa; Puvvada, Pavan Kumar; Padmavathi, Pannuru; Nallanchakravarthula, Varadacharyulu (Journal of Clinical Biochemistry and Nutrition, 2017)
The present study aimed to understand the association between erythrocyte membrane alterations and hemolysis in chronic alcoholics. Study was conducted on human male volunteers aged between 35–45 years with a drinking history of 8–10 years. Results showed that plasma marker enzymes AST, ALT, ALP and γGT were increased in alcoholic subjects. Plasma and erythrocyte membrane lipid peroxidation, erythrocyte lysate nitric oxide (NOx) levels were also increased significantly in alcoholics. Furthermore, erythrocyte membrane protein carbonyls, total cholesterol, phospholipid and cholesterol/phospholipid (C/P) ratio were increased in alcoholics. SDS-PAGE analysis of erythrocyte membrane proteins revealed that increased density of band 3, protein 4.2, 4.9, actin and glycophorins, whereas glyceraldehyde 3-phosphate dehydrogenase (GAPDH) and glycophorin A showed slight increase, however, decreased ankyrin with no change in spectrins (α and β) and protein 4.1 densities were observed in alcoholics. Moreover, alcoholics red blood cells showed altered morphology with decreased resistance to osmotic hemolysis. Increased hemolysis showed strong positive association with lipid peroxidation (r = 0.703, p<0.05), protein carbonyls (r = 0.754, p<0.05), lysate NOx (r = 0.654, p<0.05) and weak association with C/P ratio (r = 0.240, p<0.05). Bottom line, increased lipid and protein oxidation, altered membrane C/P ratio and membrane cytoskeletal protein profile might be responsible for the increased hemolysis in alcoholics.